2017
DOI: 10.1007/s11064-017-2241-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Mannose in Cultured Primary Rat Neurons

Abstract: Glucose is the main peripheral substrate for energy production in the brain. However, as other hexoses are present in blood and cerebrospinal fluid, we have investigated whether neurons have the potential to metabolize, in addition to glucose, also the hexoses mannose, fructose or galactose. Incubation of primary cerebellar granule neurons in the absence of glucose caused severe cell toxicity within 24 h, which could not be prevented by application of galactose or fructose, while the cells remained viable duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…Thus, it is reasonable to speculate that mannose kills thyroid cancer cells by this mechanism. When mannose enters into the cell, it transforms into M-6-P which accumulates when PMI enzyme activity is low, thereby decreasing cellular glycolytic levels [16,45]. As supported, our data showed that mannose treatment significantly suppressed the glycolysis of mannose-sensitive cells, while did not change that of mannose-insensitive cells.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, it is reasonable to speculate that mannose kills thyroid cancer cells by this mechanism. When mannose enters into the cell, it transforms into M-6-P which accumulates when PMI enzyme activity is low, thereby decreasing cellular glycolytic levels [16,45]. As supported, our data showed that mannose treatment significantly suppressed the glycolysis of mannose-sensitive cells, while did not change that of mannose-insensitive cells.…”
Section: Discussionsupporting
confidence: 82%
“…In the study, the KEGG annotation suggested that fructose and mannose metabolism, inositol phosphate metabolism, and Jak-STAT signaling pathway were the enriched signaling pathways among the EM, NED, and N groups. Notably, fructose and mannose metabolism and inositol monophosphatase have been identified in the CSF, , but no studies reported that it is associated with encephalitis. Additionally, the findings on Jak-STAT signaling pathway associated with the encephalitis were also supported by previous reports. …”
Section: Discussionmentioning
confidence: 99%